Special Position of ‘Aṣabah (Male Agnatic Relatives) in the Sunni Islamic Jurisprudence of Inheritance - Jalaludin, Akhmad (Asy-Syari'ah, 2024)
Abstract: This study aims to reveal the unique and privileged relationship of the position of male relatives who directly relate to the heirs or through a man without a woman ‘aṣabah or male agnatic relatives) in the Sunni Islamic jurisprudence. The Sunni Islamic jurisprudence provides a special and exclusive position to the ‘aṣabah. Whatever the extent of the kinship relationship of ‘aṣabah with the heirs, he will not be hindered except by the fellow ‘aṣabah. This study applies a socio-historical approach and uṣūl fiqh. In conclusion, the system of ‘aṣabah in the Sunni Islamic jurisprudence has resulted from an interpretation of the Qur’an and hadith, in which the weighty Arab patrilineal kinship system truly and significantly influences the interpretation.